Perceived Benefits of Micro and Small Enterprises in Developing Pro-Poor Tourism - RAY, Rudrendu; SARDAR, Sazu; TIEW, Fidella Nga Huong; ADEYINKA-OJO, Samuel Folorunso; ALIM, Md. Abdul; SOBHAN, Sanjana (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023DO - 10.14505/jemt.v14.8(72).06, 2023)
Pro-poor tourism (PPT) is revealed as a significant means of reducing poverty. However, inadequate awareness about the relationship between the poor local communities and the perceived benefits deriving from the tourism MSEs prevents the application of the PPT approach. Thus, using the Theory of Planned Behavior (TPB), this paper examines how tourism Micro and Small Enterprises (MSEs) benefit poor communities. In-depth interviews were conducted to collect data from 25 participants through semi-structured questionnaires and using NVivo12 software data was analyzed. The study found that the economic benefits focus on the standard of living, employment, tourism network and business expansion while social recognition and environmental awareness, which have a big impact on society, are marked as the novel outcomes which trigger the local communities for being engaged in tourism MSEs as non-economic benefits. This study could help the policymakers of developing countries to eradicate poverty and achieve Sustainable Development Goals 1 and 2 (Zero Poverty and No Hunger).